PENGARUH PENGGUNAAN E-TAX DAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM - Latipah, Latipah; Harahap, Baru (LPPM Universitas Putera Batam, 2019)
Tax revenues play an important role in supporting the government to improve people's welfare through the construction of public facilities. Therefore, the government always tries to increase tax revenues from year to year. One of the improvements isstheeuseeoffinformationnanddcommunicationntechnologyyby using the e-tax system andde-filing. Research using the e-tax system and e-filing on tax in the pre-batam primary school by taking a sample of 100 taxpayers, using. Data analysis method uses descriptive techniques. Variable taxpayer compliance (Y) has a constant value of 6.196 tax-payer compliancce, thissfigure indicatess if the e-filling system (X1) and e-tax system (X2) is 0, then the value of tax compliance (Y) the constant value of 6.196 has a positive and significant effect. The e-filing system variable (X1) has a regression coefficient of 0.367 etax so that the increase in the variable e-filing system is 1 unit, then the value of the tax compliance variable will increase by 0.367 e-tax units with other variables considered constant. This shows the positive relationship between e-filing system and tax payment compliance and e-filing system variable (X1) has e-filing system regression coefficient variable of 0.50 e-filing so that the e-filing system incrementing variable is 1 unit, variable value taxpayer compliance will increase by 0.505 with other variables considered